2005
DOI: 10.1080/00071660500098152
|View full text |Cite
|
Sign up to set email alerts
|

Effects of early feed restriction and cold temperature on lipid peroxidation, pulmonary vascular remodelling and ascites morbidity in broilers under normal and cold temperature

Abstract: Two experiments were conducted to evaluate the effects of early feed restriction on lipid peroxidation, pulmonary vascular remodelling and ascites incidence in broilers under normal and low ambient temperature. In experiment 1, the restricted birds were fed 8h per day either from 7 to 14 d or from 7 to 21 d, while the controlled birds were fed ad libitum. In experiment 2, the restricted birds were fed 80 or 60% of the previous 24-h feed consumption of full-fed controls for 7 d from 7 to 14 d. On d 14, half of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
39
1
6

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(52 citation statements)
references
References 28 publications
6
39
1
6
Order By: Relevance
“…Agreement with the report of Pan et al (2005), here 30% energy restriction from 19∼48 d significantly increased serum SOD activity and serum UA level, and decreased serum MDA concentration. The increased antioxidant enzymatic activity might contribute to decreased lipid peroxidation damage (Pan et al, 2005). Decreased serum MDA concentration indicated the decrease in the generation of reactive oxygen species (ROS).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Agreement with the report of Pan et al (2005), here 30% energy restriction from 19∼48 d significantly increased serum SOD activity and serum UA level, and decreased serum MDA concentration. The increased antioxidant enzymatic activity might contribute to decreased lipid peroxidation damage (Pan et al, 2005). Decreased serum MDA concentration indicated the decrease in the generation of reactive oxygen species (ROS).…”
Section: Discussionsupporting
confidence: 80%
“…Short-time feed restriction in the early growth stage of broilers has been adopted in commercial broiler production to reduce the mortality rate, the incidence of metabolic disorders such as ascites, lameness, sudden death syndrome and fat deposition (Lippens et al, 2000;Camacho et al, 2004;Pan et al, 2005). Such system results in temporary reduce of growth rate, while the normal weight of broilers can be attained on removal of feed restriction, thus improving the feed efficiency and decreasing the feeding cost (Yang et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Hepatic mitochondrial SOD activity decreased at 14 d in feedrestricted broiler chicks [136]. However, the plasma SOD activity of feed-restricted birds was markedly higher than those fed ad libitum on d 35 and d 42 [126].…”
Section: Other Environmental Stressesmentioning
confidence: 92%
“…In fact, the increase in metabolic rate at temperatures below the comfort zone (cold stress) is a significant cause of increased mortality from the pulmonary hypertension syndrome (ascites) in broilers [125]. Initially, it was shown that when broilers were exposed to a cool environment for 3 weeks, plasma SOD activity was decreased [126]. Similarly, cold exposure reduced chicken plasma SOD and supplemental L-carnitine (100 mg/kg) was shown to restore the SOD activity in cold-stressed birds [127].…”
Section: Cold Stressmentioning
confidence: 99%
“…Excessive cold stress causes a series of physiological and metabolic changes in broiler chickens, such as electrolyte and acid-base imbalances, reduced endocrine function (Olanrewaju et al, 2010), and reductions in production performance including animal feed intake, body weight and feed conversion ratio (Spinua and Degena, 1993). Cold stress also disrupts the balance of the oxidant/ antioxidant system, leading to biological membrane damage and further damaging tissue integrity and negatively influencing animal health and production (Pan et al, 2005;Mujahid and Furuse, 2009). At the same time, cold stress affects tissue structure lesions, inducing various types of disease (Sahin and Gumuslu, 2004).…”
Section: Introductionmentioning
confidence: 99%